Studi literatur: Penerapan Metode Role Playing untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Sistem Pencernaan - Salsabila, Nesa; Rangkuty, Sailana Mira; Rahma, Muthia; Harahap, Resi Susanti; Wijaya, Ramadhona; Hermaliana, Nadia (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2025)
The Role Playing method is an innovative learning approach designed to encourage active participation of learners during teaching and learning activities. This research is a literature study that analyzes various previous studies on the effectiveness of the Role Playing method in an effort to optimize the learning outcomes of students in the topic of the digestive system. The method used in this research is the literature study method, where data is collected through reference searches using Google Scholar. This research involved primary sources, such as research results, research reports and scientific articles, as well as supporting sources to complement the information. This study showed an increase in the average learning outcomes of students increased by around 80-90%. Thus, it was concluded that, especially in the digestive system material. Based on the results of the literature review, the Role Playing method is proven to be an effective teaching strategy in improving students' understanding of digestive system material. This method provides opportunities for learners to play an active role by acting out various parts of the digestive system, so that they can understand concepts more deeply through direct experience.